The Nervous System Contributes to the Tumorigenesis and Progression of Human Digestive Tract Cancer - Dayou Dai; Hao Liu (Journal of Immunology Research)
Tumors of the gastrointestinal tract are one of the highest incidences of morbidity and mortality in humans. Recently, a growing number of researchers have indicated that nerve fibers and nerve signals participate in tumorigenesis. The current overarching view based on the responses to therapy revealed that tumors are partly promoted by the tumor microenvironment (TME), endogenous oncogenic factors, and complex systemic processes. Homeostasis of the neuroendocrine-immune axis (NEI axis) maintains a healthy in vivo environment in humans, and dysfunction of the axis contributes to various cancers, including the digestive tract. Interestingly, nerves might promote tumor development via multiple mechanisms, including perineural invasion (PNI), central level regulation, NEI axis effect, and neurotransmitter induction. This review focuses on the association between digestive tumors and nerve regulation, including PNI, the NEI axis, stress, and neurotransmitters, as well as on the potential clinical application of neurotherapy, aiming to provide a new perspective on the management of digestive cancers.